2021
DOI: 10.4274/tjh.galenos.2021.2020.0695
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Antithrombin Levels in COVID-19 Patients and Impact of Fresh Frozen Plasma Treatment: A Retrospective Study

Abstract: Objective: The defective interplay between coagulation and inflammation may be the leading cause of intravascular coagulation and organ dysfunction in coronavirus disease-19 (COVID-19) patients. Abnormal coagulation profiles were reported to be associated with poor outcomes. In this study, we assessed the prognostic values of antithrombin (AT) activity levels and the impact of fresh frozen plasma (FFP) treatment on outcome. Materials and Methods: Conventional coagulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 22 publications
(10 reference statements)
2
30
0
Order By: Relevance
“…112 Antithrombin supplementation has also been a valuable measure for management of critically ill patients. 108,113 However, it is yet unknown why the acute antithrombin deficiency occurs in only some patients. Unfractionated heparin (UFH) and low-molecular-weight heparin (LMWH), the two anticoagulants that are widely used in hospitals, require antithrombin to be efficacious.…”
Section: Antithrombinmentioning
confidence: 99%
“…112 Antithrombin supplementation has also been a valuable measure for management of critically ill patients. 108,113 However, it is yet unknown why the acute antithrombin deficiency occurs in only some patients. Unfractionated heparin (UFH) and low-molecular-weight heparin (LMWH), the two anticoagulants that are widely used in hospitals, require antithrombin to be efficacious.…”
Section: Antithrombinmentioning
confidence: 99%
“…We found the article entitled “Prognostic value of antithrombin levels in COVID-19 patients and impact of fresh frozen plasma treatment: a retrospective study” very interesting [ 1 ]. Considering antithrombin (AT) levels and fresh frozen plasma (FFP) in these patients, Anaklı et al [ 1 ] concluded that “AT activity could be used as a prognostic marker for survival and organ failure in COVID-19-associated ARDS patients. AT supplementation therapy with FFP in patients with COVID-19-induced hypercoagulopathy may improve thrombosis prophylaxis and thus have an impact on survival” [ 1 ].…”
Section: To the Editormentioning
confidence: 99%
“…Considering antithrombin (AT) levels and fresh frozen plasma (FFP) in these patients, Anaklı et al [ 1 ] concluded that “AT activity could be used as a prognostic marker for survival and organ failure in COVID-19-associated ARDS patients. AT supplementation therapy with FFP in patients with COVID-19-induced hypercoagulopathy may improve thrombosis prophylaxis and thus have an impact on survival” [ 1 ]. Indeed, plasma therapy is a widely discussed alternative option for management of severe coronavirus disease-19 (COVID-19).…”
Section: To the Editormentioning
confidence: 99%
“…ATIII deficiency has been observed in COVID-19 patients in previous studies [7,9,10,14,15]. Gazzaruso et al observed that ATIII levels were lower in non-survivors amongst hospitalized COVID-19 patients and the levels were much lower in obese individuals.…”
Section: Discussionmentioning
confidence: 88%